MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UPAYA MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS SISWA SMA PADA MATERI ASAM BASA - Novi Dian Sari (Universitas Papua, Manokwari, Indonesia, 2020)
Abstact This research was conducted to see the cooperative learning model Number Head Together (NHT) on the improvement of students' critical thinking skills. This study uses a pre-experimental method. The data collection technique used observation and test methods. Observational techniques were used to observe the implementation of learning and student activities using the learning implementation observation sheet and student activity observation sheets, namely the Numbered Head Together (NHT) learning model. The test technique uses an instrument of critical thinking skills test questions in the form of essays/descriptions. The research design used One Group Pretest-Posttest Design. Keywords: critical thinking skills, student, cooperative learning model, NHT